2011
DOI: 10.1038/nbt.2050
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing 50 accessions of cultivated and wild rice yields markers for identifying agronomically important genes

Abstract: Rice is a staple crop that has undergone substantial phenotypic and physiological changes during domestication. Here we resequenced the genomes of 40 cultivated accessions selected from the major groups of rice and 10 accessions of their wild progenitors (Oryza rufipogon and Oryza nivara) to >15 × raw data coverage. We investigated genome-wide variation patterns in rice and obtained 6.5 million high-quality single nucleotide polymorphisms (SNPs) after excluding sites with missing data in any accession. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

72
751
14
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 787 publications
(843 citation statements)
references
References 59 publications
72
751
14
6
Order By: Relevance
“…We measured potential gene extinction events by estimating the number of gene families that were entirely lost in SAT while being retained in other species, and found that ∼547 genes (488 families × 1.12 genes per family) were lost in SAT after the divergence from a common ancestor with NIV. To identify gene loss events and/or novel gene creations in SAT, we performed de novo assemblies of unmapped reads from the other five AA-genome species using a previously reported methodology, with some modifications (41). We found 490 genes that were lost in the SAT genome, in agreement with the estimated number based on the loss of gene families across the AA-genome Oryza species (SI Appendix, Dataset S10a).…”
Section: Resultssupporting
confidence: 61%
“…We measured potential gene extinction events by estimating the number of gene families that were entirely lost in SAT while being retained in other species, and found that ∼547 genes (488 families × 1.12 genes per family) were lost in SAT after the divergence from a common ancestor with NIV. To identify gene loss events and/or novel gene creations in SAT, we performed de novo assemblies of unmapped reads from the other five AA-genome species using a previously reported methodology, with some modifications (41). We found 490 genes that were lost in the SAT genome, in agreement with the estimated number based on the loss of gene families across the AA-genome Oryza species (SI Appendix, Dataset S10a).…”
Section: Resultssupporting
confidence: 61%
“…Sequence diversity analysis, including PCA, dendrogram, and diversity parameters θπ and θw, were measured as described 54 . F ST values for 31 elite cultivars and 25 landraces were calculated by using population branch statistics 55 and these values were compared using FDIST 28 .…”
Section: Identification and Phylogenetic Analysis Of Nbs-lrr Genesmentioning
confidence: 99%
“…Despite the fact that rice is a major cereal and a model system for plant biology, the evolutionary origins and domestication processes of cultivated rice have long been debated. The puzzles about rice domestication include: (1) where the geographic origin of cultivated rice was, (2) which types of O. rufipogon served as its direct wild progenitor, and (3) whether the two subspecies of cultivated rice, indica and japonica, are derived from a single or multiple domestications.A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
“…A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation